Patients with chronic hepatitis C receiving treatment with direct acting antivirals: How is this population changing?. Issue 4 (April 2021) - Lombardi, Andrea; Colaneri, Marta; Vijayagopal, Kesav Aditya; Sambo, Margherita; Legnazzi, Patrizia; Sacchi, Paolo; Zuccaro, Valentina; Maiocchi, Laura; Maserati, Renato; Gulminetti, Roberto; Pagnucco, Layla; Novati, Stefano; et al.
Abstract: Background and aims: Direct acting antiviral agents (DAAs) have revolutionized the landscape of chronic hepatitis C (CHC) enabling treatment of all those infected. It remains to be determined how the characteristics of those receiving treatment are changing. Materials and methods: We retrospectively analysed all the patients with CHC who received treatment with DAAs in a large referral centre since 01/01/2015. We stratified their demographic, clinical and virological characteristics at baseline and the sustained virological response (SVR) rates according to the year of treatment. Results: In the study were included 2565 patients. During the study period, the yearly proportion of men and cirrhotic patients decreased ( p <0.001) whereas mean age increased from 59.8 to 62.2 years old ( p =0.04). An increasing trend was observed in the foreign-born patients from 4.3% to 7.9%, without reaching statistical significance. The prevalence of comorbidities had also increased during the study period ( p <0.001). Instead, the yearly number of experienced patients decreased significantly ( p <0.001) as well as the mean MELD score of cirrhotic patients from 9 to 7.6 ( p <0.001). SVR rates increased significantly, from 93.4% in 2015 to 97.1% in 2018 ( P <0.05). Conclusions: The population of patients with CHC receiving DAAs is becoming older and with more comorbidities. Nevertheless, this did not impact SVR rates.